Choice of P2Y12 inhibitor and clinical outcomes in the AUGUSTUS study: support for an individualised approach. (25th November 2020) - Storey, R; Alexander, J.H; Wojdyla, D.M; Mehran, R; Vora, A.N; Goodman, S.G; Aronson, R; Windecker, S; Granger, C.B; Lopes, R.D
Abstract: Background: AUGUSTUS randomized patients with atrial fibrillation and ACS and/or PCI to apixaban or VKA and aspirin or placebo for 6 months on background P2Y12 inhibitor. Purpose: To characterise the clinical outcomes in patients receiving clopidogrel or ticagrelor. Methods: Patients enrolled in AUGUSTUS (n=4614) were grouped by P2Y12 inhibitor at randomization. Baseline characteristics were compared among groups. Rates of ISTH major or CRNM bleeding, definite/probable stent thrombosis (ST), stroke, MI, and death or ischaemic event were quantified and treatment groups were compared according to treatment with clopidogrel or ticagrelor. Results: At randomization, patients were treated with clopidogrel (n=4165), ticagrelor (n=280), prasugrel (n=51) or no P2Y12 inhibitor (n=118). Median ages were 71, 69, 66 and 72 years (P<0.001). Ticagrelor and prasugrel were more commonly used in PCI-managed ACS (53% and 55%) whilst clopidogrel or no P2Y12 inhibitor was more common in medically-managed ACS (25% and 36%); elective PCI was the index event in 37–41% for each group. Irrespective of P2Y12 inhibitor used, bleeding risk was lower with apixaban vs. VKA and higher with aspirin vs. placebo (Table). ST rate was lowest but major/CRNM bleeding rate highest with ticagrelor + aspirin vs ticagrelor without aspirin or clopidogrel with or without aspirin. Conclusions: Apixaban is safer than VKA regardless of P2Y12 inhibitor used. Dropping aspirin reduces bleeding but is associated with numerically higher ST rates regardless of P2Y12 inhibitor used. These data support current recommendations for preferential use of NOAC vs. VKA and individualised choice of P2Y12 inhibitor and timing of aspirin cessation after PCI according to the patient's risks of bleeding and stent thrombosis. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Bristol-Myers Squibb/Pfizer